Ab-initio calculation of the physical properties of some beryllium based semiconductors - Fadla, Mohamed Abdelilah; Bentria, Bachir (Université Amar Telidji - Laghouat - Département des sciences de la matière, 2018)
The aim of this dissertation is the ab initio calculation of the properties: structural, electronic, elastic and optic of a Beryllium based ternary compounds, The calculation is conducted in the frame work of the density functional theory (DFT) used pseudo potential plane wave method (PPPW) which is implanted in the CASTEP and ABINIT codes The different physical properties calculated using the generalized gradient approximation of Perdew-Burke Ernzerhof (GGA-PBE), for calculate the band gap I used the hybrid functional HSE06 it gives a result with a high degree of reliability. All compound are a hard semiconductor with high melting temperature, BeCN2 and BeSiN2 have a large transparency domain all compounds have a good birefringence all this characteristics could make these materials useful as nonlinear crystals for many applications.